Music and ideas in the sixteenth and seventeenth centuries - Palisca, Claude V. (Studies in the history of music theory and literature, 2006)
This essential summation of Palisca's life work was nearly finished by his death in 2001, and it was brought to completion by Thomas J. Mathiesen.